Sistem Manajemen Daya Listrik Pada Pengamanan Kendaraan Berbasis Android - Hartono, Elvianto Dwi; Kridoyono, Agung; Yunanda, Anton Breva; Sidqon, Mochamad (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
The power safety system is a series of monitoring and control technologies in the form of features designed to anticipate and increase power safety for drivers and maintain the stability of the vehicle's electrical system while driving. Several power security systems are generally found in most vehicles. Power security systems are a feature in maintaining the vehicle's electrical condition in addition to security devices for a machine against criminal acts such as theft on vehicles which are increasingly common nowadays so it is hoped that it will be able to minimize the shortage of power system requirements on the machine with control and monitoring carried out using an Android-based mobile application. For this reason, this research will create a power monitoring application and security system for vehicle engines in anticipation of additional power consumption when installing engine security against criminal acts through application-based control. The output produced in this research is an Android mobile application as well as a security system device along with power consumption calculations.